Neutron reflectometry studies of aluminum–saline water interface under hydrostatic pressure. (January 2015) - Junghans, A.; Chellappa, R.; Wang, P.; Majewski, J.; Luciano, G.; Marcelli, R.; Proietti, E.
Highlights: We investigated corrosion of aluminum via neutron reflectometry. The hypothesis of an effect on corrosion due to hydrostatic pressure is confirmed. The speed of corrosion is lower in the early stage compared to results found in the literature. Nature of the corrosion compounds is investigated. Abstract: The structural stability of Al layers in contact with 3.5 wt.% NaCl water solution was investigated at a temperature of 25 °C and hydrostatic pressures from 1 to 600 atm using neutron reflectometry. A pressure–temperature (P–T) Neutron Reflectometry (NR) cell developed at Los Alamos National Laboratory (LANL) was used to understand the behavior of thin (∼900 Å) aluminum layers in contact with saline liquid. Experimental results suggest that in the preliminary stages of corrosion the influence of pressure accelerates the mechanism of interactions of the oxide film with Cl − and H2 O with lower speed compared to results found in the literature.